Plant Disease Detection Using Siamese Networks - Abbas, Rabab Farhan (Iraqi Journal of Science, 2025)
Plant sicknesses pose big challenges to crop production and food safety. Early and correct disease prognosis is crucial for powerful disease manipulation and minimizing losses. Despite the superiority of traditional strategies like visual inspection, technological advancements provide new opportunities. This paper explores the software of deep studying equipment, especially Siamese networks, for plant sickness identity in pix. Siamese networks make use of shared weights to study similarities among wholesome and diseased plant images, permitting powerful discrimination based totally on visual characteristics. This approach minimizes the need for handcrafted functions and may generalize to new diseases, making it adaptable throughout various agricultural settings. Real-time photograph processing facilitates early disease detection and intervention strategies. Comparative analysis with traditional strategies, along with CNNs and SVMs demonstrates the effectiveness of Siamese networks in plant disorder detection. Overall, this study showcases the practical application of Siamese networks for correct and well timed plant disease identity in agriculture, offering flexibility, performance, and flexibility to new sickness eventualities.